Prevalence of mental health problems in populations affected by the Ebola virus disease: A systematic review and meta-analysis. (July 2020) - Cénat, Jude Mary; Felix, Nereah; Blais-Rochette, Camille; Rousseau, Cécile; Bukaka, Jacqueline; Derivois, Daniel; Noorishad, Pari-Gole; Birangui, Jean-Pierre
Highlights: In addition to a high rate mortality, Ebola virus disease (EVD) is associated to mental health consequences. One out of five individuals exposed to EVD (survivors, families, communities, health care workers, safe and dignified burial teams, etc.) were diagnosed with depression. The results of this study provided a first level of evidence of the association between EVD and mental health problems. The global response should consider helping countries affected by EVD to develop culturally sensitive programs that address social, educational, stigma and mental health issues. Abstract: Studies have shown that, in addition to being associated with a high mortality rate, Ebola Virus Disease (EVD) is also related with mental health problems. This study aimed to determine prevalence of mental health problems and associated factors among survivors and individuals affected by EVD. A systematic review of peer-reviewed empirical studies was conducted using EMBASE, PubMed, PsycINFO and PsyARTICLES. A random effects meta-analysis was performed on the proportions of people diagnosed with depression after an EVD outbreak. Of 205 studies initially identified, 21 were included in the systematic review and 10 in the meta-analysis. Results indicated that EVD is associated with depression, anxiety, post-traumatic stress disorder, obsessive-compulsive disorder, among others. Results revealed that one person out of five affected to EVD has been diagnosed with depression (standardized mean difference 19.92%, 95% CI 10.43%; 34.70). The I 2 provided evidence of heterogeneity in the results. This study demonstrated the evidence of the impact of EVD on the mental health of survivors and individuals affected by EVD. Further studies should consider the mental health consequences of EVD to plan culturally sensitive prevention and intervention programs based on the experience of communities affected by EVD.